Knowledge and practice of blood transfusion amony final year nursing students in Universiti Sains Malaysia (USM) - Mansor, Nurul Ain (2020)
Blood transfusion is a potentially hazardous procedure. Stringent procedures must be followed to ensure that the correct blood is given to the recipient. The aim of this study was to access the knowledge and practice on blood transfusion of final year nursing students which are diploma students and degree students in Universiti Sains Malaysia. A cross-sectional study was undertaken involving 66 participants via random sampling. A questionnaire survey was used for data collection from February 2020 to March 2020. Chi-square test was employed to examine the association between selected socio demographic characteristics and level of knowledge and practice of blood transfusion. The mean age of the respondent was 22.12 (1.13) years, with range between 21 years old up to 24 years old. The findings revealed that the majority of respondents, 66.7% of diploma students and 51.5% of degree students had moderate knowledge of blood transfusion. For practice, the findings revealed that the majority of respondents, 84.8% of diploma students and 97.0% of degree students had good practice of blood transfusion. A statistically significant association was observed between selected socio-demographic (programme) and level of knowledge (p<0.156) and with level of practice (p<0.087). It can be concluded that the nursing students is lack of knowledge on blood transfusion. The study emphasizes the need of knowledge and practice for performing the blood transfusion procedure.